2013
DOI: 10.1371/journal.pone.0066272
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Organizing Model of the Visual Development of Hand-Centred Representations

Abstract: We show how hand-centred visual representations could develop in the primate posterior parietal and premotor cortices during visually guided learning in a self-organizing neural network model. The model incorporates trace learning in the feed-forward synaptic connections between successive neuronal layers. Trace learning encourages neurons to learn to respond to input images that tend to occur close together in time. We assume that sequences of eye movements are performed around individual scenes containing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…Gain-modulated neurons in PPC have been found to generate depth-dependent activity (Blohm & Crawford, 2012) as well as hand-centered maps (Galeazzi et al, 2013) but because our setup does not have vergence and tactile information, we will not focus on these properties. Instead, we propose to use the gain-field neurons to estimate each incoming signal from the fusion of all, in their respective reference frame.…”
Section: Generalization From Visuomotor Associationmentioning
confidence: 99%
“…Gain-modulated neurons in PPC have been found to generate depth-dependent activity (Blohm & Crawford, 2012) as well as hand-centered maps (Galeazzi et al, 2013) but because our setup does not have vergence and tactile information, we will not focus on these properties. Instead, we propose to use the gain-field neurons to estimate each incoming signal from the fusion of all, in their respective reference frame.…”
Section: Generalization From Visuomotor Associationmentioning
confidence: 99%
“…The same VisNet architecture was used in our previous simulations of the development of hand-centred visual neurons using trace learning [33–35]. However, in the simulations reported below, we implement a Hebbian learning rule in the model instead of the trace rule.…”
Section: Methodsmentioning
confidence: 99%
“…The synaptic connections between the successive layers of neurons are updated using associative learning. Although VisNet has been often used to model invariance in the ventral visual stream, it has been subsequently applied to simulate visual processes occurring in the dorsal stream (Rolls and Stringer, 2007 ; Galeazzi et al, 2013 ; Rolls and Webb, 2014 ). Both ventral and dorsal streams share architectural similarities, each consisting of a hierarchical series of neuronal layers with competition mediated by inhibitory interneurons within each layer (Rolls and Webb, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…A self-organizing hypothesis to account for how hand-centered representations could occur has been recently proposed (Galeazzi et al, 2013 ). Here, it was suggested that while the eyes are exploring a visual scene involving a target object in a fixed position with respect to the hand, a form of trace learning would allow the network to associate different views of the same hand-object spatial configuration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation